Interaktif “Bamboozle” terhadap Minat Belajar Sejarah Siswa Kelas XI di SMA PL Don Bosko - Noviyani Damanik; Atno Atno (Jurnal Kajian dan Penelitian Umum, 2026)
This study aims to analyze the effectiveness of using the interactive learning media Baamboozle on the history learning interest of Grade XI students at SMA PL Don Bosko. The research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The sample consisted of 64 students divided into two groups: an experimental group (32 students) using Baamboozle and a control group (32 students) using conventional methods. The data collection instrument was a learning interest questionnaire that had been validated with a Cronbach’s Alpha reliability coefficient of 0.87. The data were analyzed using an independent sample t-test with a significance level of 0.05. The results showed a significant difference in history learning interest between the experimental group and the control group (t = 4.823; p = 0.000 < 0.05). The mean score of learning interest in the experimental group (82.4) was higher than that of the control group (68.7). In conclusion, the interactive learning media Baamboozle is proven to be effective in increasing the history learning interest of Grade XI students at SMA PL Don Bosko. These findings have positive implications for history teachers to integrate digital gamification platforms into the learning process.